Pengaruh konsentasi maltodekstrin terhadap karakteristik fisik dan kimia susu kambing bubuk menggunakan metode drum dryer - Thevia Nur Afriani Sutiana Putri; Atia Fizriani; Triana Ulfah; Susilowati; Gumelar Retno Palupi; Hasmo Sadewo; Hari Hariadi; Sandi Darniadi (COMPOSITE : Jurnal Ilmu Pertanian, 2026)
The complex nutritional content of goat milk is classified as a food product that is susceptible to spoilage. This is due to the growth of microorganisms, particularly pathogenic bacteria. Therefore, processing fresh milk into powdered milk is one way to preserve the nutrients in milk. The addition of ingredients such as maltodextrin is necessary to serve as a carrier agent in the drying process. The objective of this study is to determine the effect of maltodextrin addition on the physical and chemical characteristics of goat milk powder using a drum dryer method. In this study, a Randomized Block Design (RBD) was used with four different treatments based on variations in maltodextrin concentration, namely 5%, 10%, 15%, and 20%, each repeated twice to ensure the validity of the results. The data obtained were analyzed to assess the effect of the treatments on various quality parameters, such as moisture content, ash content, protein content, carbohydrate content, solubility, yield, fat content, and hygroscopic properties. The results of the analysis of goat milk powder with maltodextrin addition using the drum dryer method in treatment P4 were moisture content (2.40%), ash content (3.41%), protein (10.16), fat (29.51%), carbohydrate (56.92), hygroscopicity (30.31%), solubility (90.02), and yield (98.93). The addition of maltodextrin to the physical and chemical characteristics of goat milk powder did not significantly affect the hygroscopicity but significantly affected the moisture content, ash content, protein, fat, carbohydrates, solubility, and yield.